FACTORS OF ACHIEVING THE MODERN QUALITY OF PEDAGOGICAL ACTIVITY OF STUDENTS OF PRESCHOOL EDUCATION. (Scientific journal of the Fergana State University, 2024)
The main condition for the development of the preschool education system is the training of teaching staff with professional competence. It is important to create the necessary conditions for achieving modern quality of preparation of students for teaching activities, to develop pedagogical technologies aimed at changing the internal position of the future teacher, his social and semantic definition as the main condition for the acceptance and development of his pedagogical ideas.